Implementation of Sacrificial Worship in the Government Environment Pamekasan Regency Islamic Law Perspective - Hosen; Siti Mudmainah (Al Ahkam, 2023)
This study aims to determine the implementation of sacrificial worship in the Pamekasan Regency Government Environment. This research uses empirical legal research methods that use a type of socio-legal research with an Islamic law approach. The data collection used semi-structured interviews, non-participant observations, and document studies. The primary data source is from respondents who are directly involved in the implementation of sacrificial worship in the Pamekasan Regency Government. The rest is sought from secondary data in the form of a review of books related to this research topic. The sacrificial animals collected came from Regional Apparatus Organizations and vertical agencies in Pamekasan. The sacrificial animals were collected above the names of each agency without the name of the employee as the person who sacrificed even through the agency. Two problems are the main study in this study, namely: First, how to carry out sacrificial worship within the Pamekasan Regency Government. Second, how is the review of Islamic law on the implementation of sacrificial worship within the Pamekasan Regency Government. And this study produced, first; the implementation of sacrificial services carried out within the Pamekasan Regency Government in the form of collecting, slaughtering, and distributing them according to the rules set by the Pamekasan Regency Government. Second; because sacrificial animals are collected and slaughtered on behalf of agencies and not on behalf of their employees, according to Islamic law it does not include sacrificial worship in accordance with the provisions of sharia law but is counted as almsgiving